2022
DOI: 10.1186/s12871-022-01577-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active forced air warming during the first hour after anesthesia induction and intraoperation avoids hypothermia in elderly patients

Abstract: Background The study aimed at exploring an optimal temperature model of forced air warming during the first hour after induction and intraoperation to prevent hyperthermia for elderly patients undergoing laparoscopic abdominal surgery. Methods There were 218 patients that were randomly divided into 3 groups warmed with a forced-air warmer during surgery: Group L (intraoperative warming set to 38 °C, n = 63), Group H (intraoperative warming set to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…multimodal analgesia, preoperative education [20][21][22][23], intraoperative heat preservation [24][25][26], GDFT(Goal-directed uid therapy) [7,27,28] and stress reduction in ERAS.…”
Section: Discussionmentioning
confidence: 99%
“…multimodal analgesia, preoperative education [20][21][22][23], intraoperative heat preservation [24][25][26], GDFT(Goal-directed uid therapy) [7,27,28] and stress reduction in ERAS.…”
Section: Discussionmentioning
confidence: 99%
“…An age older than 65 years was another risk factor for postoperative hypothermia, as suggested in previous studies [ 16 , 17 ]. Elderly patients, particularly those who are over 65 years old, have less effective regulatory ability of their central nervous system and an increased susceptibility to hypothermia [ 9 ]. As mentioned above, many MT patients possess risk factors for hypothermia, including poor nutritional status, low BMI and advanced age; thus, it is necessary for us to take active measures to prevent hypothermia in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many medical specialty societies have provided guidelines for hypothermia prevention, which recommend monitoring the patient's body temperature and providing active warming interventions throughout the perioperative period [7,8]. However, despite the development of some effective active warming techniques, such as forced-air warming systems, self-warming mattresses, and irrigation and infusion of warmed fluids [9][10][11][12], a survey of 6 Asia-Pacific countries showed that compliance with international perioperative temperature management guidelines in the Asia-Pacific remains poor, especially in small hospitals [13].…”
Section: Introductionmentioning
confidence: 99%
“…Higher temperatures of the forced-air warming device increase the probability of skin damage [13]. Patient satisfaction was higher when adjusting the temperature of the forced-air warming device from a high temperature (42°C) to a medium temperature (38°C) intraoperatively [14].…”
Section: Discussionmentioning
confidence: 99%